Effect of Dielectric Constant of Solvents on the Particle Size and Bandgap of La/SnO2‐TiO2 Nanoparticles and Their Catalytic Properties. Issue 12 (25th October 2016) - Farrukh, Muhammad Akhyar; Muneer, Iqra; Butt, Komal Mehmood; Batool, Sadaf; Fakhar, Nazia
Abstract : Lanthanum (La) supported on tin oxide‐titanium oxide (SnO2 ‐TiO2 ) nanoparticles were prepared by a sol–gel method followed by a hydrothermal method. Effect of different solvents (ethyl acetate, benzyl alcohol, ethylene glycol) on the particle size and catalytic activity was investigated. The nanomaterial was characterized by transmission electron microscopy, powder X‐ray diffraction, scanning electron microscopy, fourier transform infrared spectroscopy, and energy dispersive X‐ray. The catalytic and optical properties were studied using solid‐phase spectrophotometry and ultraviolet–visible spectroscopy, respectively. Gas chromatography‐mass spectrometry (GC‐MS) was used to detect the intermediates during the catalytic degradation of methylene blue. It was observed that with decrease in the dielectric constant ( ε ) of the solvent, the bandgap and particle size decrease and catalytic efficiency increases. Hence, the highest catalytic activity was observed with the solvent having the least dielectric constant. Abstract : Lanthanum (La) supported on tin oxide‐titanium oxide (SnO2 ‐TiO2 ) nanoparticles were prepared by a sol–gel method followed by a hydrothermal method. Effect of ethyl acetate, benzyl alcohol, and ethylene glycol solvents on the particle size and catalytic activity was investigated. It was observed that with the decrease in dielectric constant of the solvent, the bandgap and particle size decrease and the catalytic efficiency increases.